2013
DOI: 10.1177/070674371305800709
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging and Suicide: A Systematic Review

Abstract: Objective: To systematically review the research on the association between sense of belonging and suicide. Method:We systematically reviewed electronic databases for studies that included assessments of suicidality and belonging. Results:We found 16 studies that met our eligibility criteria. They all found an association between belonging and suicidality but nearly all of the studies were in nonclinical populations, and the association was weak and could be taken into account by confounding factors.Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 24 publications
3
36
0
3
Order By: Relevance
“…Adolescents who report a strong familial connection, with greater parental involvement and emotional support, are less likely to attempt suicide (Flouri & Buchanan, 2002;Israelashvili et al, 2006). A sense of social belonging, or connectedness to others, is linked to decreased risk for suicidal behavior (Hatcher & Stubbersfield, 2013) and, as well, sense of connectedness, or perception of interpersonal closeness, may also buffer risk. Among two college samples, students who reported fewer social ties or confidants experienced greater suicidal ideation and suicide-related behavior (Whitlock et al, 2011;Whitlock, Wyman, & Barreira, 2012).…”
Section: Protective Factors: Points Of Intervention To Decrease Suicimentioning
confidence: 99%
“…Adolescents who report a strong familial connection, with greater parental involvement and emotional support, are less likely to attempt suicide (Flouri & Buchanan, 2002;Israelashvili et al, 2006). A sense of social belonging, or connectedness to others, is linked to decreased risk for suicidal behavior (Hatcher & Stubbersfield, 2013) and, as well, sense of connectedness, or perception of interpersonal closeness, may also buffer risk. Among two college samples, students who reported fewer social ties or confidants experienced greater suicidal ideation and suicide-related behavior (Whitlock et al, 2011;Whitlock, Wyman, & Barreira, 2012).…”
Section: Protective Factors: Points Of Intervention To Decrease Suicimentioning
confidence: 99%
“…With the disintegration of the seniority system, there has been an evolution to an intensely competitive society and a distancing from the traditionally harmonious Japanese sense of group belonging . It has been suggested that a lack of a sense of belonging could be behind the increase in middle–older‐age suicide . With regards to MTD, the problem of such a sense of belonging may be another major consideration.…”
Section: Sociocultural Aspectsmentioning
confidence: 99%
“…belonging could be behind the increase in middleolder-age suicide. 38,39 With regards to MTD, the problem of such a sense of belonging may be another major consideration. In the corporate world, younger employees who do not have such a sense of belonging and exhibit aspects of depression at work are often able to function normally and happily with such a sense on weekends, at places of leisure and/or online (Facebook, etc.…”
Section: Sociocultural Aspectsmentioning
confidence: 99%
“…In support of this theory, research has indicated that belongingness is inversely associated with suicide ideation and attempts [68]. Hatcher and Stubbersfield’s [9] systematic review of research on the association between belongingness and suicidality found that research in this area generally has reported an inverse relationship between belongingness and suicidality, with lower levels of belongingness predicting higher risk of suicide ideation and attempts.…”
Section: Interpersonal Theory Of Suicidementioning
confidence: 99%